Decision Support System for Selection of Quality Doves with Web-Based Analytical Hierarchy Process (AHP) Methods - Ardhian Ramadhan; Suprianto; Sumarno; Rohman Dijaya (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of making this system is to make it easier for breeders and pigeon lovers to determine high quality pigeons. The method used is the analytical hierarchy process (AHP), this method is used to support completing the program, using the analytical hierarchy process method, using the analytical hierarchy process method. this is because it can make it easier to make decisions. The result of this system is a web-based system that supports windows and linux operating systems, the purpose of making this system is to facilitate the decision making of high pigeons in determining quality pigeons that are integrated with database storage. The benefit of using this system is to facilitate the decision-making process for quality pigeons.